TEACHERS’ AND STUDENTS’ VIEWS ON THE USE OF SONGS IN TEACHING AND LEARNING IONIC BONDS - Odhiambo, Daniel; Edward, WINSTON (Proceedings of the International Conference on Education, 2022)
Taking into consideration learner engagement during a chemistry lesson is a very crucial step if conceptual understanding is one of the goals. In the current times, teachers are drastically losing a grasp of their learners during lessons, especially chemistry lessons. However, studies that borrowed from the kindergartens have proved that incorporation of songs during lessons may engage learners. This qualitative research, which took an action research design, explored the feasibility of applying songs in rich science content in enhancing interest, motivation and engagement in ionic bonding and similar chemistry concepts among Kenyan high school students. The aim of the study was to transform the attitudes of learners towards chemistry through the use of songs and to increase learner participation during chemistry lessons. The study used Two purposively sampled chemistry teachers and 60 purposively sampled form two learners. From the 60 learners, 8 were chosen through random sampling to take part in focus group discussion (FGD). Multiple tools including interview protocols, lesson observation protocols and focus group discussion protocols were employed for data collection. Findings revealed that songs enhanced learner engagement during the lesson, captured learner attention, enhanced recall abilities of the learners, and restored their positive attitudes towards chemistry. Additionally, it was found that songs promoted diverse learner preferences and learning extension outside the classroom. The study recommends that schools should advocate for use of songs as one of the instruction strategies in the classroom since it has a very high potential of engaging learners and sparking their interest towards learning of chemistry. The findings of this study are intended to inform curriculum developers from various contexts on the formation of a policy that guides the use of songs as high school classroom teaching strategies.